Influence of Dimensionless Parameter on De-Ionized Water-alumina Nanofluid Based Parabolic Trough Solar Collector - Gopalsamy, Vijayan; Rajasekaran, Karunakaran; Kamaraj, Logesh; Sivasaravanan, Siva; Kok, Metin (Recent Patents on Nanotechnology, 2019)
Background: Aqueous-alumina nanofluid was prepared using magnetic stirrer and ultrasonication process. Then, the prepared nanofluid was subjected to flow through the unshielded receiver of the parabolic trough solar collector to investigate the performance of the nanofluid and the effects of the dimensionless parameter were determined. Methods: The experimental work has been divided into two sections. First, the nanofluid was prepared and tested for its morphology, dimensions, and sedimentation using X-Ray Diffraction and Raman shift method. Then, the nanofluids of various concentrations from 0 to 4.0% are used as heat transfer fluid in unshielded type collector. Finally, the effect of the dimensionless parameter on the performance was determined. Results: For the whole test period, depending upon the bulk mean temperature, the dimensionless parameters such as Re and Nu varied from 1098 to 4552 & 19.30 to 46.40 for air and 2150 to 7551 & 11.11 to 48.54 for nanofluid. The enhancement of thermal efficiency found for 0% and 4.0% nanoparticle concentrations was 32.84% for the mass flow rate of 0.02 kg/s and 13.26% for the mass flow rate of 0.06 kg/s. Conclusion: Re and Nu of air depend on air velocity and ambient temperature. Re increased with the mass flow rate and decreased with concentration. Heat loss occurred by convection mode of heat transfer. Heat transfer coefficient and global efficiency increased with increased mass flow rate and volume fraction. The thermal efficiency of both 0% and 4.0% concentrations became equal for increased mass flow rate. It has been proven that at high mass flow rates, the time available to absorb the heat energy from the receiver is insufficient.
Keywords: heat removal